2007
DOI: 10.4049/jimmunol.179.4.2467
|View full text |Cite
|
Sign up to set email alerts
|

Icsbp1/IRF-8 Is Required for Innate and Adaptive Immune Responses against Intracellular Pathogens

Abstract: The chronic myeloid leukemia syndrome of the BXH-2 mouse strain (Mus musculus) is caused by a recessive mutation (R294C) in the transcriptional regulator Icsbp1/IRF-8. In trans activation assays using an IL-12p40 gene reporter construct introduced in RAW 264.7 mouse macrophages, we show that the Icsbp1C294 isoform behaves as a partial loss-of-function. The Icsbp1C294 hypomorph allele appears to have a threshold effect on IL-12 production, with pleiotropic consequences on resistance to different types of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…It has previously been reported that MyD88-mediated activation of NF-B, IRF1, and IRF8 are required for IL-12p35 and IL12p40 gene expression and driving Th1 responses (17)(18)(19)(20). However, these studies failed to find a role for these transcriptional factors in IL-23-driven Th17 responses and suggested that alternative signaling molecules may be involved (18,20).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It has previously been reported that MyD88-mediated activation of NF-B, IRF1, and IRF8 are required for IL-12p35 and IL12p40 gene expression and driving Th1 responses (17)(18)(19)(20). However, these studies failed to find a role for these transcriptional factors in IL-23-driven Th17 responses and suggested that alternative signaling molecules may be involved (18,20).…”
Section: Discussionmentioning
confidence: 45%
“…However, the induction of IL-12 and IL-23 are differentially regulated by TLR and NOD-like receptor-activated DC (7). NF-B, IFN regulatory factor (IRF)1, and IRF8 signaling pathways play important roles in the expression of IL12p35 and IL-12p40 and in driving Th1 responses (17)(18)(19)(20). In contrast, it has been demonstrated that IL-6 and IL-23 production in DC by agonists of dectin-1, and consequent development of Th17 cells, is mediated by signaling via Syk and CARD9 (21).…”
Section: Nterleukin-17-producing T Cells (Th17 Cells) and Ifn-␥-secmentioning
confidence: 99%
“…However, IL-21 KO mice are unable to control P. chabaudi parasitemia (88). Not surprisingly, the absence of CD8 + DC in this infection results in impaired parasite control and more pronounced relapses (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another study analyzing CD4 + T cell responses to P. chabaudi Ag showed CD8 + DC as superior to CD8 2 DC at MHC II presentation in the steady-state, but the latter were more efficient during infection (39). In the P. chabaudi model, mice devoid of CD8 + DC developed higher peaks of parasitemia and more pronounced relapses than did their WT counterparts (40). These results suggested an important role for CD8 + DC in the development of T cell responses against blood-stage malaria parasites.…”
mentioning
confidence: 99%
“…43,44 Similarly, mice carrying a mutation in IRF-8 (BXH-2) are extremely susceptible to P. chabaudi. 45 Therefore, uncontrolled early parasite replication in the AcB62 strain could be linked to an impaired early inflammatory response and/or dampened polarization of the critical, early Th1 response. 46 The minimal Char10 region is large, B20 Mb; numerous genes associated with the innate or protective immune response map within Char10.…”
Section: Discussionmentioning
confidence: 99%